Impact of the cefazolin shortage on the selection and cost of parenteral antibiotics during the supply disruption period in Japan: A controlled interrupted time series analysis - Hiroyuki Nagano; Jung-ho Shin; Susumu Kunisawa; Kiyohide Fushimi; Miki Nagao; Yuichi Imanaka (Journal of Infection and Public Health, 2023)
Background: A serious shortage of cefazolin (CEZ) occurred in Japan in 2019. We compared the impact of the CEZ shortage on the selection of parenteral antibiotics at affected and non-affected hospitals. Methods: The data were extracted from a nationwide Japanese administrative database and included all hospitalized cases between April 2016 and December 2020. We defined ‘hospitals with shortage’ as those hospitals with a statistically significant decrease in the use of CEZ during the supply disruption period compared to the same months of the previous year; other hospitals as ‘hospitals without shortage’. We determined the proportion of each selected parenteral antibiotic use to the sum of all selected antibiotic use in the two groups of hospitals during the supply disruption period and during the same months of the previous year. A controlled interrupted time series (CITS) analysis was conducted to estimate the impact of the CEZ shortage on each antibiotic use and the cost of all parenteral antibiotics per patient day in hospitals with shortage as compared to those without shortage. Results: In the hospitals with shortage, the proportion of CEZ use to the sum of all selected antibiotics decreased (23.5–11.1%). The decrease in CEZ use was mainly offset by the use of ceftriaxone, ceftriaxone, and ampicillin/sulbactam. The CITS analysis showed a statistically significant increase in the use of broader-spectrum beta-lactams and clindamycin during the supply disruption period (flomoxef up 58.1%, cefotiam up 63.1%, cefmetazole up 14.5%, ceftriaxone up 13.9%, and clindamycin up 20.1%). The analysis showed no statistically significant change in the cost of all parenteral antibiotics per patient day. Conclusions: During the CEZ supply disruption, there was a statistically significant increase in the use of broader-spectrum beta-lactams and clindamycin in hospitals with shortage compared with those without shortage.